Purinergic Receptors in Neurological Diseases With Motor Symptoms: Targets for Therapy - Oliveira-Giacomelli, Ágatha; Naaldijk, Yahaira; Sardá-Arroyo, Laura; Gonçalves, Maria C. B.; Corrêa-Velloso, Juliana; Pillat, Micheli M.; de Souza, Héllio D. N.; Ulrich, Henning (Frontiers in Pharmacology, 2018)
Since proving ATP functions as a neurotransmitter in neuron/glia interactions, the purinergic system has been more intensely studied within the scope of the central nervous system. In neurological disorders with associated motor symptoms, including Parkinson’s disease (PD), motor neuron diseases (MND), multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), Huntington’s Disease (HD), restless leg syndrome (RLS) and ataxias, alterations in purinergic receptor expression and activity have been noted, indicating a potential role for this system in disease etiology and progression. In neurodegenerative conditions, neural cell death provokes extensive ATP release and alters calcium signaling through purinergic receptor modulation. Consequently, neuroinflammatory responses, excitotoxicity and apoptosis are directly or indirectly induced. This review analyzes currently available data which suggests involvement of the purinergic system in neuro-associated motor dysfunctions and underlying mechanisms. Possible targets for pharmacological interventions are also discussed.